Novel Aspects of Nucleolar Functions in Plant Growth and Development - Munetaka Sugiyama (Frontiers Research Topics, 2018)
The nucleolus is a prominent nuclear domain that is common to eukaryotes. Since the nucleolus was first described in the 1830s, its identity had remained a mystery for longer than 100 years. Major advances in understanding of the nucleolus were achieved through electron microscopic and biochemical studies in the 1960s to 1970s followed by molecular biological studies. These studies finally established the view of the nucleolus that it is a large aggregate of RNA-protein complexes associated with the rRNA gene region of chromosome DNA, serving mainly as a site of ribosome biogenesis, where pre-rRNA transcription, pre-rRNA processing, and ribosome assembly occur. This function of the nucleolus appears to indicate that the nucleolus plays a constitutive and essential role in fundamental cellular activities by producing ribosomes. Recent research has shown, however, that the nucleolus is more dynamic and can have more specific and wider functions. In plants, nucleolar functions have been implicated in developmental regulations and environmental responses by accumulating pieces of evidence obtained mostly from genetic studies of nucleolar factor-related mutants. Comprehensive analysis of nucleolar proteins and molecular cytological characterization of sub-nucleolar and peri-nucelolar bodies have also provided new insights into behaviors and functions of the plant nucleolus. In this Research Topic, we would like to collect physiological and molecular links between the nucleolus to plant growth and development, shed light on novel aspects of nucleolar functions beyond its classical view, and stimulate research activities focusing on the nucleolus across various fields of plant science, including molecular biology, cell biology, genetics, developmental biology, physiology, and evolutionary biology.